Suppression of microRNAs targeting key MEP pathway genes affects plastid terpenoid content and photosynthesis under variable light conditions - Syed Muhammad Iqbal Syed Othman; Arif Faisal Mustaffa; Muhammad Sajad; Muhamad Hafiz Che-Othman; Hoe-Han Goh; Ismanizan Ismail (Molecular Biology Reports, 2026)

Suppression of miR426 enhances photoprotection and chlorophyll stability via upregulation of ELIP2 in Arabidopsis thaliana - Arif Faisal Mustaffa; Syed Muhammad Iqbal Syed Othman; Nur Irdina Izzatie Mohd Zahid; M. Hafiz Che-Othman; Hoe-Han Goh; Muhammad Sajad; Ismanizan Ismail (Molecular Biology Reports, 2026)

A semi-implicit fully Eulerian WENO scheme for high-fidelity Vlasov–Ampère simulations - Mao-Syun Wong; Shih-Hung Chen; Tsung-Che Tsai; Kun-Han Lee (Computer Physics Communications, 2026)

Synergistic bulk–interfacial regulation for wide-temperature aqueous zinc batteries - Yuanhang Wang; Hui Zhi; Yiming Zhang; Chenglin Miao; Yicheng Tan; Junzhi Li; Jiacheng Zhou; Che Yuan; Mengjie Lu; Wei Han (Chemical Engineering Journal, 2026)

Geometrically consistent ordinal mixture-of-experts for weight estimation of sows from multi-view point clouds - Qiang Zhai; Longhu Ma; Han Jiang; Li Wan; Yunhan Liu; Yiran Liao; Yifeng Yang; Changmeng Peng; Jinglan Lei; Yong Zhuo; Lianqiang Che; De Wu (Computers and Electronics in Agriculture, 2026)

Assessing multidimensional changes in human settlements across urban regeneration paradigms: A case study of Wuhan, China - Meng-Tian Han; Qian Cao; Hai-Yun Xu; Xiang-Wen Deng; Lun-Che Wang; Jun Wan (Sustainable Cities and Society, 2026)

Amorphous CO2-philic molecular networks via covalent coupling for high-performance TFC hollow fiber membranes - Meta Mamo Goro; Zelalem Gudeta Abdi; Qing-Yun Chou; Ching-Han Chou; Che-Wei Chang; Tai-Shung Chung (Chemical Engineering Journal, 2026)

Heterochromatin protein 1 (HP1) dysfunction drives male-biased sex ratio in Trichogramma dendrolimi (Hymenoptera: Trichogrammatidae) via paternal genome elimination during mitosis - Zhi-chao Jia; Hong-yu Liang; Yu-han Xu; Ning He; Wu-nan Che; Yue Shi; Hui Dong (Chromosome Research, 2026)

Concentration and depth-resolved analysis of transition metals in atmospheric particles: A combined approach using X-ray fluorescence and synchrotron radiation single-particle imaging - Yiliang Liu; Jiawei Zhou; Hanxiong Che; Difei Zhang; Pingping Wen; Yifan Zhao; Xin Du; Lingshuo Meng; Yan Han; Zhier Bao; Xin Qi; Xin Long; et al. (Journal of Environmental Sciences, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

A gradient boosting-based machine learning framework for improving atmospheric visibility numerical prediction - Chen Han; Hong Wang; Ke Gui; Xutao Zhang; Wenjie Zhang; Yue Peng; Yang Zhao; Zhaodong Liu; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

The CMA Chemistry–Weather Coupled Model and Its Operational Forecast of Fog–Haze and Sand/Dust Storms - Hong Wang; Xiaoye Zhang; Wenjie Zhang; Yue Peng; Ping Wang; Hongli Liu; Zhaorong Zhuang; Liping Huang; Weihong Tian; Yang Zhao; Ke Gui; Chen Han; et al. (Journal of Meteorological Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Temperature sensitivity and rainfall heat flux drive rapid mass loss of low-latitude glaciers in the Southeastern Qinghai–Tibet Plateau - Yanjun Che; Shijin Wang; Yun Cao; Weiwei Lv; Xinggang Ma; Congzheng Han; Jian Zhong; Rong Wu (CATENA, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

Luteolin-stabilized pickering emulsion for encapsulating Enterococcus hirae: preparation, characterization, and synergistic effects on hyperuricemia - Chengtao Han; Songhao Che; Hui-Min Li; Yan-Yu Chi; Jun-Yan Xiang; Qiuhong Xie; Hongyu Xiang (Food Research International, 2026)

Effects of prenatal exposure to hexafluoropropylene oxide dimer acid on rat and offspring mammary gland development and associated hormone levels - Lu Liu; Wendong Liu; Libing Wang; Wenjing Zhu; Dongmei Jia; Yuxin Lin; Zhugen Yang; Kui Che; Wenchao Han (Chemico-Biological Interactions, 2026)

La-mediated green rust for synergistic nitrogen–phosphorus removal and targeted N2 formation regulated by built-in electric field and spin state - Yibo Zhang; Jun Nan; Chen Liang; Zhencheng Ge; Han Deng; Yanhan Che; Yunhao Pan; Meng Li; Bohan Liu (Water Research, 2026)

Inverse Rayleigh wave dispersion curves via improving artificial fish swarm algorithm - Chengwei Zhang; Hongyan Shen; Han Che; Hao Wang; Shisheng Feng; Kanglogn Wang (Acta Geophysica, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

A novel approach for utilizing UAV imaging and deep learning techniques for river channel measurement and flood simulation - Jen-Yu Han; Chun-Jia Huang; Yuan-Shun Chang; Yen-Cheng Lin; Hao-Che Ho (Geomorphology, 2026)

A novel fructan from Atractylodes macrocephala ameliorates ulcerative colitis through gut microbiota-mediated PI3K/Akt signaling - Jiangping Wu; Qiangbao Xu; Yiping Yang; Zhu Yang; Zihan Li; Lingzhi Chen; Yujia Song; Hui Che; Guodong Wang; Qiuyue Lv; Jun Han (Carbohydrate Polymers, 2026)

Design and performance verification of crab seedling automatic counting equipment based on improved YOLOv11+DeepSORT - Changfeng Tian; Xuan Che; Lei Ge; Zhi Qu; Mengxia Han (Aquacultural Engineering, 2026)

mRNA Rather than Protein Expression of Hepatic Selenoprotein H is More Sensitive to Short-term Low Aflatoxin B1 Exposure in Mice with Varying Selenium Intake - Ruirui Yu; Mengru Hao; Aiping Liu; Chenggang Yang; Ping Xu; Yong Zhou; Alexey A. Tinkov; Aolin Yang; Qingqing Lv; Ziyu Han; Chao Wang; Zhou Wang; et al. (Biological Trace Element Research, 2026)

Mechanisms of cavitation erosion risk enhancement by vortex generators at lower Reynolds numbers - Ning Qiu; Haitao Rao; Doubin Xun; Han Zhu; Baowei Shan; Bangxiang Che; Peng Wu (Ocean Engineering, 2026)

Evaluation of salt tolerance in Agropyron Gaertn.: key indicators, optimal conditions, and implications for crop improvement - Jiarui Zou; Jing Yang; Ying Liu; Yanping Yang; Lai Wei; Haiming Han; Shenghui Zhou; Weihua Liu; Jinpeng Zhang; Lihui Li; Yonghe Che (Genetic Resources and Crop Evolution, 2026)

Anthraquinone sites engineering of covalent organic frameworks enables efficient and selective 1O2 generation via directed oxidation of peroxymonosulfate - Yuzheng Wu; Jinyi Tan; Zifan Li; Luwen Liang; Bing Chen; Xinwen Ou; Shan Yao; Guiquan Che; Youqun Wang; Bin Han (Journal of Hazardous Materials, 2025)

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Machine learning-enhanced meta-analysis unravels the global patterns of microplastic-heavy metal co-toxicity in terrestrial ecosystems - Hai-han Jiang; Tian-Hao Che; Qing Su; Bin Jin; Yan Lu; Han-Xi Zhou; Min-Jie Fu; Jing-Ya Zhou (Environmental Pollution, 2025)

Diurnal Characteristics and Sources Apportionment of Atmospheric PM2.5 in a Medium-sized City in East China - Lingshuo Meng; Yang Du; Hanxiong Che; Jiawei Zhou; Zhier Bao; Yiliang Liu; Yan Han; Xin Qi; Sainan Wang; Xin Long; Yang Chen (Aerosol Science and Engineering, 2025)

Hydrofoil cavitation noise signatures under inflow velocity modulation - Han Zhu; Ning Qiu; Pei Xu; Bangxiang Che; Doubin Xun; Yifu Gong; Shuai Yang (Ocean Engineering, 2025)

New method for separating and online detecting polydisperse mixed nanoplastics - Huachao Che; Han Wang; Liqiang Lu; Yunjie Huang; Xike Tian; Xiaochen Wang; Weimin Xie; Yeukuang Hwu (Journal of Hazardous Materials, 2025)

Acid-activated hexagonal boron nitride efficiently accelerates the photocatalytic decomposition of perfluoroalkyl substances: the mediation of chlorine radical - Yi-Chin Hsieh; Ming-Han Yang; Pin-Fei Chu; Chia-Hsuan Kao; Paul Westerhoff; Wen-Che Hou (Chemical Engineering Journal, 2025)

Aquimarina rhodophyticola sp. nov. and Aquimarina besae sp. nov., Isolated from Marine Red Algae - Jeong Min Kim; Byeong Jun Choi; Hülya Bayburt; Dong Min Han; Che Ok Jeon (Current Microbiology, 2025)

Facile synthesis of α-Fe2O3/ Fe3O4 hybrid adsorbent with tailored affinity sites for high-efficiency microplastics capture - Che Han; Yujie Wang; Jintao Liu; Qiangyi Deng; Hongmei Zhang; Shuang Xu; Conglu Zhang (Journal of Environmental Chemical Engineering, 2025)

Development and multi-objective optimization of a solar-powered hybrid aerator for aquaculture - Zhi Qu; Changfeng Tian; Xuan Che; Mengxia Han; Yin Zhou (Aquacultural Engineering, 2025)

Determination of the deposition of urban submicron aerosols in the human respiratory tract considering hygroscopic growth - Aoyuan Yu; Jiayuan Lu; Xiaojing Shen; Xinyao Hu; Yangmei Zhang; Quan Liu; Hongfei Tong; Linlin Liang; Lei Liu; Qianli Ma; Lujie Han; Huizheng Che; et al. (Atmospheric Environment, 2025)

Effect of water vapor on the structure and performance of silver catalysts for ethylene oxidation - Yandong Chu; Hongmei Liang; Qiang Lin; Haoyang Huang; Ping Che; Yongsheng Han (Chemical Engineering Journal, 2025)

Effects of the southwest vortex on the vertical structure of ozone in the Sichuan Basin in China - Huiqiong Ning; Hong Wang; Ping Kang; Zhaodong Liu; Yue Peng; Wenjie Zhang; Chen Han; Yang Zhao; Wei Liu; Ping Wang; Huizheng Che (Atmospheric Pollution Research, 2025)

Microwave-induced strength reduction and weakening mechanisms of basic rocks - Zhongjun Ma; Xiaobao Zhao; Han Li; Hanwen Liu; Yangwei Long; Yanlong Zheng; Ping Che (International Journal of Rock Mechanics and Mining Sciences, 2025)

Numerical simulation of GPR via Leapfrog ADI-FDTD - Bohua Wang; Hongyan Shen; Han Che; Shuai Liu; Chi Wang; Chengwei Zhang; Hao Wang; Shisheng Feng; Kanglong Wang (Journal of Applied Geophysics, 2025)

Experimental study of pressure distribution and wave forces on pile groups under extreme waves - Xi Yu; Jiajia Wang; Wanshui Han; Lili Xiao; Xin Xu; Kai Zhou; Silu Che; Xiaokun Chen; Mengqi Xia (Ocean Engineering, 2025)

Chiral nanostructured Pd films for efficient electrocatalytic reduction of nitrite to ammonia - Hao Chen; Quanzheng Deng; Tianwei Ouyang; Wanning Zhang; Bin Liu; Lu Han; Shunai Che; Yuxi Fang (Chemical Engineering Journal, 2025)

Study on the contribution of the major desert groups on SDS weather in East Asia combining the model simulation and multiple observations - Huiqiong Ning; Hong Wang; Zhaodong Liu; Yue Peng; Wenjie Zhang; Chen Han; Yang Zhao; Ping Wang; Hailin Gui; Jikang Wang; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2025)

Risks of respiratory and circulatory system diseases induced by exposure to PM2.5 in high humidity and low solar radiation environments: disease types, genes, and functions - Xiaomeng Li; Liru Zhang; Zhengliang Zhang; Xuan Li; Jingli Qian; Jiawei Zhou; Hanxiong Che; Yan Han; Xin Qi; Fumo Yang; Yu Huang; Chao Peng; et al. (Environmental Geochemistry and Health, 2025)

Poly(vinylidene fluoride)-based Janus separators with an ultrathin conductive layer for suppressing lithium dendrite growth - Ruiqi Che; Sha Cheng; Cheng Huang; Ming Liu; Zhongao Chen; Jin Han; Wen Chen; Pengchao Zhang (Chemical Engineering Journal, 2025)

Bridging the gap between hyperspectral imaging and crop breeding: soybean yield prediction and lodging classification with prototype contrastive learning - Guangyao Sun; Yong Zhang; Lei Wang; Longyu Zhou; Shuaipeng Fei; Shiteng Han; Shunfu Xiao; Yingpu Che; Long Yan; Yun Xu; Yinghui Li; Lijuan Qiu; et al. (Computers and Electronics in Agriculture, 2025)

Development and characterization of novel wood-based composite materials for solar-powered atmospheric water harvesting: A machine intelligence supported approach - Xingying Zhang; Yangyang Xu; Shenjie Han; Xiang Weng; Wenbo Che; Kongjie Gu; Ying Guan; Youming Yu; Derek Hao; Junfeng Hou (Journal of Cleaner Production, 2025)

Molecular characterization of TRAF gene family in snakehead (Channa argus) - Xiu Feng Han; Ming Yue Che; Xue Su; Jing Yun Tian; Lan Hao Liu; Pin Nie; Su Wang (Fish & Shellfish Immunology, 2025)

Comprehensive validation of a compact laser speckle contrast imaging system for vascular function assessment: from the laboratory to the clinic - Meng-Che Hsieh; Chia-Yu Chang; Ching-Han Hsu; Congo Tak Shing Ching; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Inversion of Rayleigh wave dispersion curves integrating the Osprey–Cauchy and Pigeon-inspired optimization algorithm - Shuai Liu; Hongyan Shen; Han Che; Bohua Wang; Chi Wang; Chengwei Zhang; Guangzhou Shao; Shisheng Feng; Hao Wang; Kanglong Wang (Acta Geophysica, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

High-precision U-series dating of Panxian Dadong hominin site, Guizhou Province, southwestern China - Xiaochao Che; Fei Han; Xingsheng Zhang; Bo Cao; Ping Xiao; Guanjun Shen; Jianxin Zhao (Quaternary Science Reviews, 2025)

Possible role of autophagy in microbial volatile pollutant-induced starch degradation and expression of hypoxia responsive genes - Chung-Chih Huang; Ching-Han Chang; Tu-Trinh Thi Truong; Wu-Guei Wang; Che-Hui Lin; Chih-Yun Chiang; Iwai Obayashi; Hao-Jen Huang (Environmental Pollution, 2025)

Eco-friendly lamellar structured graphene oxide-Lysine nanocomposite membranes with varying d-spacing for enhanced pervaporation desalination - Shalligito Habetamu Abebe; Hannah Faye M. Austria; T.M. Subrahmanya; Huai-Che Chang; Tsung-Han Huang; Gabriel V. Carballo; Wei-Song Hung; Chien-Chieh Hu; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

Three-dimensional oriented Ca nanoporous carbon with N doping tuned via self-assembly to potentiate P adsorption: The vital role of the micro interfacial electronic environment - Yibo Zhang; Jun Nan; Fangmin Wu; Xuesong Ye; Zhencheng Ge; Li He; Yanhan Che; Han Deng; Yunhao Pan; Bohan Liu (Journal of Cleaner Production, 2025)

Numerical Simulation and Experimental Study of a Small-Scale Vacuum Fish Pump - Changfeng Tian; Zhi Qu; Xuan Che; Mengxia Han; Yin Zhou; Fan Wu (Journal of Marine Science and Engineering, 2024)
The existing vacuum fish pump is too large and difficult to move, which is difficult to apply to small fishing vessels. However, the development of a small vacuum fish pump is not a single scaling of the existing vacuum fish pump but requires the support of relevant experiments and simulation theories. In this study, a vacuum fish pump suitable for small fishing vessels was developed. Firstly, a numerical model of the internal flow field during the vacuum fish pump’s working process was established using computational fluid dynamics (CFDs) and verified its effectiveness by physical experiments. It is found that the VOF model can well predict the variation of the volume fraction of the liquid phase in the whole calculation area with time during the suction or drainage process of the vacuum fish pump. Then, the internal flow field characteristics of the fish pump under different working conditions were simulated, and the rationality of the design of the fish pump was evaluated according to the numerical results. Finally, a separate physical experiment was carried out on grass carp, carp, crucian carp, silver carp, and bighead carp, respectively, and the capture efficiency and corresponding fish damage rate for different fish were analyzed. The experimental and numerical results show that the vacuum suction fish pump can achieve efficient and automatic suction and transport of live fish.

Characteristics and health risks assessment of PM2.5-bound heavy metals during winter in urban areas of northern China: A case study in Kaifeng - Xin Qi; Yan Han; Hanxiong Che; Jiawei Zhou; Chao Peng; Zhier Bao; Yiliang Liu; Lingshuo Meng; Shumin Zhang; Fumo Yang; Wenbo Xue; Yu Lei; et al. (Science of The Total Environment, 2024)

Organic carbon decomposition temperature sensitivity positively correlates with the relative abundance of copiotrophic microbial taxa in cropland soils - Yuan Du; Anlan Yu; Yuan Chi; Zelin Wang; Xinrui Han; Kaifang Liu; Qiuping Fan; Xin Hu; Rongxiao Che; Dong Liu (Applied Soil Ecology, 2024)

Chemical regulation of lignin spatial conformation for a multifunctional soft material with a novel energy dissipation mechanism - Yingying Su; Xiao Han; Guanda Che; Jinghui Zhou; Yao Li; Sheng Cheng; Cong Wang; Xu Fei (Chemical Engineering Journal, 2024)

Fabrication of carbon-coated iron-based porous heterogeneous Fenton catalyst and enhanced degradation performance towards ciprofloxacin - Yufan Mo; Chunxia Che; Wei Han; Feiran Chen; Jun Guan; Feng Zhang; Bo Yang; Xiangdong Ren; Huiyu Li; Saeed Ahmed; Yongjun Feng (Chemical Engineering Journal, 2024)

Enhanced sensitivity of spectral CT imaging in vivo by using Ytterbium chelate - Chunmei Yang; Didi Gu; Xin Zhu; Pan Han; Liping Pan; Xiaoling Che; Xinyao Chen; Qiuyu Meng; Guidong Dai; Lu Yang (Chemical Engineering Journal, 2024)

Mechanical behavior of immersed tunnel under the influence of differential settlements: A case study of GZ tunnel - Chao Su; Ailan Che; Ziyao Xu; Zhaolong Han; Feng Zhu; Tong Hai (Tunnelling and Underground Space Technology, 2024)

Impact of re-entrant jet and shedding cloud cavity on the distribution of cavitation erosion - Ning Qiu; Doubin Xun; Han Zhu; Pei Xu; Bangxiang Che; Minwei Li; Wenjie Zhou (Ocean Engineering, 2024)

Monitoring nonlinear large gradient subsidence in mining areas through SBAS-InSAR with PUNet and Weibull model fusion - Yuanjian Wang; Ximin Cui; Chunqing Ge; Yuhang Che; Yuling Zhao; Peixian Li; Yue Jiang; Xiaoqing Han (Environmental Science and Pollution Research, 2024)

The genetic basis and process of inbreeding depression in an elite hybrid rice - Xiaodong Xu; Yawen Xu; Jian Che; Xu Han; Zhengji Wang; Xianmeng Wang; Qinghua Zhang; Xu Li; Qinglu Zhang; Jinghua Xiao; Xianghua Li; Qifa Zhang; et al. (Science China Life Sciences, 2024)

Determination of major drive of ozone formation and improvement of O3 prediction in typical North China Plain based on interpretable random forest model - Liyin Yao; Yan Han; Xin Qi; Dasheng Huang; Hanxiong Che; Xin Long; Yang Du; Lingshuo Meng; Xiaojiang Yao; Liuyi Zhang; Yang Chen (Science of The Total Environment, 2024)

Biogenic volatile organic compounds dominated the near-surface ozone generation in Sichuan Basin, China, during fall and wintertime - Dasheng Huang; Qing Li; Yan Han; Shi-Yong Xia; Jiawei Zhou; Hanxiong Che; Keding Lu; Fumo Yang; Xin Long; Yang Chen (Journal of Environmental Sciences, 2024)

Report on the 4th Board Meeting of the International Human Phenome Consortium - Mei Tian; Han Liu; Shiwen Peng; Zhong Yang; Weishuo Tao; Huiting Che; Xuanxuan Gao; Li Jin (Phenomics, 2024)

Comparative pangenome analysis of Aspergillus flavus and Aspergillus oryzae reveals their phylogenetic, genomic, and metabolic homogeneity - Dong Min Han; Ju Hye Baek; Dae Gyu Choi; Min-Seung Jeon; Seong-il Eyun; Che Ok Jeon (Food Microbiology, 2024)

Characterization of Organosulfates (OSs) in typical urban areas in Eastern China: Source, Process, and Volatility - Yang Du; Hanxiong Che; Zier Bao; Yiliang Liu; Qing Li; Miao Hu; Jiawei Zhou; Shumin Zhang; Xiaojiang Yao; Quan Shi; Chunmao Chen; Yan Han; et al. (Atmospheric Research, 2024)

QTL mapping for agronomic traits in Agropyron Gaertn. CP population at the flowering stage - Yonghe Che; Jing Yang; Yutong He; Nan Song; Yanping Yang; Lai Wei; Xinming Yang; Yannong Zhang; Jinpeng Zhang; Haiming Han; Xiuquan Li; Shenghui Zhou; et al. (Euphytica, 2024)

Exposure to polystyrene nanoplastics induces apoptosis, autophagy, histopathological damage, and intestinal microbiota dysbiosis of the Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Haojuan Yuan; Na Rihan; Mingming Han; Xingguo Liu; Tian Zhu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Interaction mechanism between cloud cavitation and micro vortex flows - Ning Qiu; Han Zhu; Bangxiang Che; Wenjie Zhou; Yuxing Bai; Chuan Wang (Ocean Engineering, 2024)

Water pollution scenarios and response options for China - Haoyuan Feng; Joep F. Schyns; Maarten S. Krol; Mengjie Yang; Han Su; Yaoyi Liu; Yongpeng Lv; Xuebin Zhang; Kai Yang; Yue Che (Science of The Total Environment, 2024)

Characterization of risks and pathogenesis of respiratory diseases caused by rural atmospheric PM2.5 - Ronghua Zhang; Xiaomeng Li; Xuan Li; Qin Zhang; Jiancai Tang; Zhenzhong Liu; Guiqin Song; Li Jiang; Fumo Yang; Jiawei Zhou; Hanxiong Che; Yan Han; et al. (Science of The Total Environment, 2024)

Unraveling the carbohydrate metabolic characteristics of Leuconostoc mesenteroides J18 through metabolite and transcriptome analyses - Ju Hye Baek; Dong Min Han; Dae Gyu Choi; Che Ok Jeon (Food Chemistry, 2024)

Vegetable residues retention: An effective and environment friendly way to handle tomato wastes from greenhouse production - Xiaomei Sun; Sijin Chen; Huan Li; Jinxia Li; Guojun Han; Haobing Dong; Jiangwei Che; Qin Zhang (European Journal of Soil Biology, 2024)

Corrigendum to “Source area morphometry and high depletion rate of landslides may indicate their coseismic origin” [Engineering Geology 330 (2024) 107424] - Ivo Baroň; Jan Jelének; Jan Klimeš; Jia-Jyun Dong; Rostislav Melichar; Martin Šutjak; Yichin Chen; Che-Ming Yang; En-Lun Zhang; Joanna Méndez; Chia-Han Tseng; Filip Hartvich; et al. (Engineering Geology, 2024)

The application study of the revised IMPROVE atmospheric extinction algorithm in atmospheric chemistry model focusing on improving low visibility prediction in eastern China - Chen Han; Hong Wang; Yue Peng; Zhaodong Liu; Wenjie Zhang; Yang Zhao; Huiqiong Ning; Ping Wang; Huizheng Che (Atmospheric Research, 2024)

Post-transcriptional regulation of myogenic transcription factors during muscle development and pathogenesis - Shen-Liang Chen; Chuan-Che Wu; Ning Li; Tzu-Han Weng (Journal of Muscle Research and Cell Motility, 2024)

The ability of energy commodities to hedge the dynamic risk of epidemic black swans - I-Chun Tsai; Han-Bo Chen; Che-Chun Lin (Resources Policy, 2024)

Source area morphometry and high depletion rate of landslides may indicate their coseismic origin - Ivo Baroň; Jan Jelének; Jan Klimeš; Jia-Jyun Dong; Rostislav Melichar; Martin Šutjak; Yichin Chen; Che-Ming Yang; En-Lun Zhang; Joanna Méndez; Chia-Han Tseng; Filip Hartvich; et al. (Engineering Geology, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Polyoxygenated cyclohexene derivatives and other constituents of Uvaria rufa stem - Aleksandra Gurgul; Zhenlong Wu; Kyu-Yeon Han; Gauri Shetye; Kongmany Sydara; Onevilay Souliya; Jeremy J. Johnson; Chun-Tao Che (Phytochemistry, 2023)

Effect of micro vortex generators on cavitation collapse and pressure pulsation: An experimental investigation - Ning Qiu; Pei Xu; Han Zhu; Yifu Gong; Bangxiang Che; Wenjie Zhou (Ocean Engineering, 2023)

Rebuilding high-quality near-surface ozone data based on the combination of WRF-Chem model with a machine learning method to better estimate its impact on crop yields in the Beijing-Tianjin-Hebei region from 2014 to 2019 - Tian Han; Xiaomin Hu; Jing Zhang; Wenhao Xue; Yunfei Che; Xiaoqing Deng; Lihua Zhou (Environmental Pollution, 2023)

Detection of micro-plasma-induced exosomes secretion in a fibroblast-melanoma co-culture model - Han Lee; Jiunn-Der Liao; Tak-Wah Wong; Che-Wei Wu; Bo-Yao Huang; Shun-Cheng Wu; Pei-Lin Shao; Yu-Han Wei; Ming-Hsien Cheng (Analytica Chimica Acta, 2023)

Piperlongumine induces apoptosis and autophagy via the PI3K/Akt/mTOR pathway in KB human cervical cancer cells - Eun-Ji Han; Eun-Young Choi; Su-Ji Jeon; Sang-Woo Lee; Jun-Mo Moon; Soo-Hyun Jung; Bumseok Kim; Sung-Dae Cho; Jeong-Seok Nam; Changsun Choi; Jeong-Hwan Che; Ji-Youn Jung (Food and Chemical Toxicology, 2023)

Photocatalysis-PMS oxidation system based on CQDs-doped carbon nitride nanosheets for degradation of residual drugs in water - Yongqiang Wang; Yibo Bai; Che Han; Zaimei Li; Xiaowen Lun; Conglu Zhang (Environmental Science and Pollution Research, 2023)

Investigation on the adsorption characteristics of pharmaceuticals and personal care products on polyethylenimine-alginate-activated carbon composite fiber - Se-Been Mun; Minhee Han; Yub Raj Dangi; Bo-Gyeon Cho; Se-Ra Jin; Kwan-Yong Lee; Che-Ryong Lim; Chul-Woong Cho; Yeoung-Sang Yun (Desalination, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Liang-Chun Wang; Li-Hsuan Chen; Yu-Che Chiu; Chung-Yi Liou; Han-Chung Chen; Chia-Yun Lu; Jian-Lin Chen (Fish & Shellfish Immunology, 2023)

Springtime reactive volatile organic compounds (VOCs) and impacts on ozone in urban areas of Yunnan-Guizhou plateau, China: A PTR-TOF-MS study - Qing Li; Yan Han; Dasheng Huang; Jiawei Zhou; Hanxiong Che; Liuyi Zhang; Keding Lu; Fumo Yang; Yang Chen (Atmospheric Environment, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Production and analysis of metabolites from solid-state fermentation of Chenopodium formosanum (Djulis) sprouts in a bioreactor - Chen-Che Hsieh; Shu-Han Yu; Kai-Wen Cheng; Yu-Wei Liou; Cheng-Chih Hsu; Chang-Wei Hsieh; Chia-Hung Kuo; Kuan-Chen Cheng (Food Research International, 2023)

The characteristics and metabolic potentials of the soil bacterial community of two typical military demolition ranges in China - Keyu Yao; Anjuan Cai; Jin Han; Ruijie Che; Jiarong Hao; Fenghe Wang; Mao Ye; Xin Jiang (Science of The Total Environment, 2023)

Fermentative features of Bacillus velezensis and Leuconostoc mesenteroides in doenjang-meju, a Korean traditional fermented soybean brick - Dong Min Han; Ju Hye Baek; Byung Hee Chun; Che Ok Jeon (Food Microbiology, 2023)

Chitinophaga horti sp. nov., Isolated from Garden Soil - Dong Min Han; Ju Hye Baek; Dae Gyu Choi; Myeong Seo Jin; Che Ok Jeon (Current Microbiology, 2023)

SO2 resistance of CeO2- and Co3O4-supported activated carbon during removal of mercury from flue gas: A comparative study - Shengji Wu; Yalun Ma; Wangsheng Yu; Hui Wang; Wei Yang; Lei Che; Zhongxi Han (Fuel, 2023)

Report on the 3rd Board Meeting of the International Human Phenome Consortium - Mei Tian; Han Liu; Shunling Chen; Zhong Yang; Weishuo Tao; Shiwen Peng; Huiting Che; Li Jin (Phenomics, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

The protective effect of Eleutheroside E against the mechanical barrier dysfunction triggered by lipopolysaccharide in IPEC-J2 cells - Huijuan Li; Rui Han; Feng Yong; Yueli Fan; Bao Zhao; Xiaocai Hu; Tianrui Zhang; Dongsheng Che (Research in Veterinary Science, 2023)

Environmental, economic, and energy analysis of municipal solid waste incineration under anoxic environment in Tibet Plateau - Zeng Dan; Yuechi Che; Xutong Wang; Peng Zhou; Zhiyong Han; Duo Bu; Xuebin Lu; Wenchao Ma; Guanyi Chen (Environmental Research, 2023)

Development and characterization of microsatellite markers for the rubber tree powdery mildew pathogen Oidium heveae - Qiaohui Han; Yongxiang He; Haiyan Che; Daquan Luo; Jonathan S. West; Xueren Cao (European Journal of Plant Pathology, 2022)

Transcriptome analysis reveals the effects of strigolactone on shoot regeneration of apple - Sumeera Asghar; Yao Xiong; Meng Che; Xingqiang Fan; Hui Li; Yi Wang; Xuefeng Xu; Wei Li; Zhenhai Han (Plant Cell Reports, 2022)

Genome-wide characterization and expression analysis of SAUR gene family in Melon (Cucumis melo L.) - Ze Tian; Jiadi Han; Gen Che; Agula Hasi (Planta, 2022)

Dual Drug Loaded pH-sensitive Micelles for Efficient Bacterial Infection Treatment - Yingxian Chen; Qian Zhao; Junhua Han; Xinmiao Lan; Jing Che; Meiwan Chen; Xing-Jie Liang; Xiaowei Ma (Pharmaceutical Research, 2022)

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Notch activation suppresses endothelial cell migration and sprouting via miR-223-3p targeting Fbxw7 - Ruonan Wang; Ziyan Yang; Liang Liang; Xingxing Feng; Bo Che; Xiaoyan Zhang; Qijun Zheng; Xianchun Yan; Hua Han (In Vitro Cellular & Developmental Biology - Animal, 2022)

Microbacterium sulfonylureivorans sp. nov., isolated from sulfonylurea herbicides degrading consortium - Qingyun Ma; Delong Kong; Qi Zhang; Miaomiao Li; Xiaoyan Han; Juan Che; Yiqing Zhou; Wei Zhang; Xu Jiang; Zhiyong Ruan (Archives of Microbiology, 2022)

Characterization of municipal solid waste incineration and flue gas emission under anoxic environment in Tibet Plateau - Zeng Dan; Wenwu Zhou; Peng Zhou; Yuechi Che; Zhiyong Han; A Qiong; Bu Duo; Xuebin Lv; Qiongda Zhuoma; Jing Wang; Wang Yang; Guanyi Chen (Environmental Science and Pollution Research, 2022)

Nanotechnology advances in pathogen- and host-targeted antiviral delivery: multipronged therapeutic intervention for pandemic control - Kai-Chieh Yang; Jung-Chen Lin; Hsiao-Han Tsai; Chung-Yao Hsu; Vicky Shih; Che-Ming Jack Hu (Drug Delivery and Translational Research, 2021)

High-order conservative and oscillation-suppressing transport on irregular hexagonal grids - Han Jiao; Xindong Peng; Yuzhang Che; Jun Chang (Meteorology and Atmospheric Physics, 2021)

Unraveling Physiological and Metabolomic Responses Involved in Phlox subulata L. Tolerance to Drought Stress - Yan Xiong; Yanting Qu; Hui Han; Fei Chen; Li Li; Huanwei Tang; Daidi Che; Xing Zhang (Plant Molecular Biology Reporter, 2021)

Spike-sorting analysis of neural electrical signals evoked by acupuncture based on model - Qing Qin; Yajiao Liu; Bonan Shan; Yanqiu Che; Chunxiao Han; Yingmei Qin; Ruofan Wang; Jiang Wang (Cognitive Neurodynamics, 2021)

Bacterial community composition in soils covered by different vegetation types in the Yancheng tidal marsh - Jie Fang; Yongcui Deng; Rongxiao Che; Cheng Han; Wenhui Zhong (Environmental Science and Pollution Research, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Optimization of air quality monitoring network based on a spatiotemporal-spectrum manifold analysis - Chi-Fang Wang; Ming-Che Hu; Chieh-Han Lee; Hwa-Lung Yu (Stochastic Environmental Research and Risk Assessment, 2019)

Model tests on thermo-mechanical behavior of an improved energy pile - Han-long Liu; Cheng-long Wang; Gang-qiang Kong; Charles W.W. Ng; Ping Che (European Journal of Environmental and Civil Engineering, 2018)

A corn straw-based diet increases release of inflammatory cytokines in peripheral blood mononuclear cells of dairy cows - Yan-yi Che; Xiao-jing Xia; Bo-ping He; Yuan-yuan Gao; Wen-bo Ren; Hong-tao Liu; Jian-fang Liu; Ting-hao Huang; Wen-yu Han; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2018)

Vibrational resonance in a randomly connected neural network - Yingmei Qin; Chunxiao Han; Yanqiu Che; Jia Zhao (Cognitive Neurodynamics, 2018)

Novel TBX22 mutations in Chinese nonsyndromic cleft lip/palate families - Jiewen Dai; Chen Xu; Guomin Wang; Yun Liang; Teng Wan; Yong Zhang; Xiaofeng Xu; Lebin Yu; Zonggang Che; Qiqing Han; Dandan Wu; Yusheng Yang (Journal of Genetics, 2018)

Pricing weather index insurance based on artificial controlled experiment: a case study of cold temperature for early rice in Jiangxi, China - Qing Sun; Zaiqiang Yang; Xianghong Che; Wei Han; Fangmin Zhang; Fang Xiao (Natural Hazards, 2018)

Metrical Consistency NMF for Predicting Gene–Phenotype Associations - Shuai Han; Hong Cai; Dan Che; Yaogong Zhang; Yalou Huang; Maoqiang Xie (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Notch ligand Delta-like1 enhances degranulation and cytokine production through a novel Notch/Dok-1/MAPKs pathway in vitro - Songsong Jiang; Yifan Da; Shiwen Han; Yahong He; Huilian Che (Immunologic Research, 2018)

Distinct Histone Modifications Modulate DEFB1 Expression in Human Vaginal Keratinocytes in Response to Lactobacillus spp. - Jaehyouk Lee; Ara Jang; Jin Wook Kim; Jun Hyun Han; Byung Hee Chun; Hye Su Jung; Che Ok Jeon; Soon Chul Myung (Probiotics and Antimicrobial Proteins, 2017)

Identification and validation of major QTLs and epistatic interactions for seed oil content in soybeans under multiple environments based on a high-density map - Qi Zhaoming; Zhang Xiaoying; Qi Huidong; Xin Dawei; Han Xue; Jiang Hongwei; Yin Zhengong; Zhang Zhanguo; Zhang Jinzhu; Zhu Rongsheng; Hu Zhenbang; Liu Chunyan; et al. (Euphytica, 2017)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Elucidation of anti-Vibrio factors associated with green alga Picochlorum sp. strain S1b - Jung-Che Kuo; Yu-Han Chang; Tsung-Yuan Chen; Yi-Min Chen (Journal of Applied Phycology, 2015)

A method of detecting contamination events using multiple conventional water quality sensors - Shuming Liu; Han Che; Kate Smith; Chao Chen (Environmental Monitoring and Assessment, 2015)

An ephaptic transmission model of CA3 pyramidal cells: an investigation into electric field effects - Xile Wei; Yinhong Chen; Meili Lu; Bin Deng; Haitao Yu; Jiang Wang; Yanqiu Che; Chunxiao Han (Cognitive Neurodynamics, 2014)

Elevated expression of vascular endothelial growth factor (VEGF) 120 in parthenogenetic porcine placentas - Yang Han; Hongsheng Ouyang; Dongsheng Che; Xianju Chen; Yongye Huang; I. A. Elfaki elhag; Daxin Pang; Zhanjun Li (Biotechnology Letters, 2014)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

Removal of Trihalomethanes and Haloacetic Acids from Treated Drinking Water by Biological Activated Carbon Filter - Jie-Chung Lou; Che-Jung Chang; Wei-Hsiang Chen; Wei-Bin Tseng; Jia-Yun Han (Water, Air, & Soil Pollution, 2014)

A proposal to unify two subspecies of Staphylococcus equorum: Staphylococcus equorum subsp. equorum and Staphylococcus equorum subsp. linens - Do-Won Jeong; Hye-Rim Kim; Seulhwa Han; Che Ok Jeon; Jong-Hoon Lee (Antonie van Leeuwenhoek, 2013)

Investigation of EEG abnormalities in the early stage of Parkinson’s disease - Chun-Xiao Han; Jiang Wang; Guo-Sheng Yi; Yan-Qiu Che (Cognitive Neurodynamics, 2013)

Soil organic C, nutrients, microbial biomass, and grain yield of rice (Oryza sativa L.) after 18 years of fertilizer application to an infertile paddy soil - Meirong Lv; Zhongpei Li; Yuping Che; F. X. Han; Ming Liu (Biology and Fertility of Soils, 2011)